Diurnal variations of NO2 tropospheric vertical column density over the Seoul metropolitan area from the Geostationary Environment Monitoring Spectrometer (GEMS): seasonal differences and the influence of the a priori NO2 profile - S. Seo; S.-W. Kim; S.-W. Kim; K.-M. Kim; A. Richter; K. Lange; J. P. Burrows; J. Park; J. Park; H. Hong; H. Lee; U. Jeong; et al. (Atmospheric Measurement Techniques)
The Geostationary Environment Monitoring Spectrometer (GEMS), launched in 2020, provides both temporally and spatially continuous air quality data from geostationary Earth orbit (GEO). This study first investigates the seasonal variations and diurnal behavior of nitrogen dioxide (NO2) tropospheric vertical column densities (TropVCDs) over the Seoul metropolitan area (SMA) using GEMS data, retrieved by the IUP-UB algorithm. We find that the magnitude of the NO2 TropVCDs and their diurnal behavior have significant seasonal dependences. In January, the highest NO2 TropVCD values in the range 27.5–28.9×1015 molec.<mspace width="0.125em" linebreak="nobreak"/>cm-2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="60pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="326fae219ada504ce6e38a4700ad9e74"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-115-2025-ie00001.svg" width="60pt" height="13pt" src="amt-18-115-2025-ie00001.png"/></svg:svg> during the four seasons were observed at 15:00 local time (LT) and NO2 TropVCD increases from the first retrieved values at 10:00 LT. On the other hand, we find the lowest values (7.4–8.8×1015 molec.<mspace width="0.125em" linebreak="nobreak"/>cm-2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="60pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="321f0654a1dbc06a9dc99dc1771b5ee4"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-115-2025-ie00002.svg" width="60pt" height="13pt" src="amt-18-115-2025-ie00002.png"/></svg:svg>) are at ∼14:00 LT in July. The VCD values in July increased up to 10:00 LT and then decreased until 14:00 LT but then began to increase again. These different diurnal behaviors of the TropVCDs in the different seasons reflect the differences in photochemical and meteorological conditions as well as the emissions of NOx. Photochemical transformations are typically more rapid in July and slower in January. The absolute values and diurnal behavior of NO2 TropVCDs are significantly influenced by the wind speed, except in July. Moderate (wind speed ≥3 m s−1) or strong wind (wind speed >5 m s−1) reduced the magnitude of the diurnal behavior in January, implying that the NO2 plumes were transported downwind. Finally, we compared the retrieved NO2 TropVCDs by using different a priori NO2 data simulated by TM5 and WRF-Chem, calculated using the most recent emission inventories. Although simulated VCDs from WRF-Chem and TM5 show differences of up to a factor 2.75, retrieved NO2 TropVCDs using each a priori data have almost identical values and diurnal behaviors, except in July. Notably, the diurnal behavior of the retrieved NO2 TropVCDs is independent of that from the two chemical transport models, indicating that observations of slant column densities are the dominant factor in determining the diurnal behavior of NO2 TropVCDs. Changes in the model horizontal resolution and volatile organic compound (VOC) emission inventory do not significantly affect the retrieved NO2 TropVCDs in this study. However, when the a priori NO2 vertical profile was fixed as the values at 13:45 LT, the diurnal patterns of NO2 TropVCDs showed significant changes, with differences of up to −18.3 %.